Epicuticular wax accumulation and regulation of wax pathway gene expression during bioenergy Sorghum stem development - Chemelewski, Robert; McKinley, Brian A.; Finlayson, Scott; Mullet, John E. (Frontiers in Plant Science, 2023)
Bioenergy sorghum is a drought-tolerant high-biomass C4 grass targeted for production on annual cropland marginal for food crops due primarily to abiotic constraints. To better understand the overall contribution of stem wax to bioenergy sorghum's resilience, the current study characterized sorghum stem cuticular wax loads, composition, morphometrics, wax pathway gene expression and regulation using vegetative phase Wray, R07020, and TX08001 genotypes. Wax loads on sorghum stems (~103-215 µg/cm 2 ) were much higher than Arabidopsis stem and leaf wax loads. Wax on developing sorghum stem internodes was enriched in C28/30 primary alcohols (~65%) while stem wax on fully developed stems was enriched in C28/30 aldehydes (~80%). Scanning Electron Microscopy showed minimal wax on internodes prior to the onset of elongation and that wax tubules first appear associated with cork-silica cell complexes when internode cell elongation is complete. Sorghum homologs of genes involved in wax biosynthesis/transport were differentially expressed in the stem epidermis. Expression of many wax pathway genes (i.e., SbKCS6, SbWSD1, SbABCG12, SbABCG11) is low in immature apical internodes then increases at the onset of stem wax accumulation. SbCER4 is expressed relatively early in stem development consistent with accumulation of C28/30 primary alcohols on developing apical internodes. High expression of two SbCER3 homologs in fully elongated internodes is consistent with a role in production of C28/30 aldehydes. Gene regulatory network analysis aided the identification of sorghum homologs of transcription factors that regulate wax biosynthesis (i.e., SbSHN1, SbWRI1/3, SbMYB94/96/30/60, MYS1) and other transcription factors that could regulate and specify expression of the wax pathway in epidermal cells during cuticle development.